Political system of Bosnia and Herzegovina, 1995-2005 : power-sharing in theory and practice - Karic, Mirsad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
The primary aim of this study is to examine and analyze the political system of Bosnia and Herzegovina (1995-2005) which emerged from the Dayton Peace Agreement (DPA). Power-sharing (consociational) model which emphasizes the role of the political elites is used as the most appropriate approach in order to study post-Dayton Bosnia and Herzegovina. The study identifies factors that are conducive to cooperative behavior of domestic elite. These factors are: nature of social cleavages, size of various ethnic groups and segmental isolation. Elite behavior is examined in terms of a grand collation, segmental autonomy, proportional representation and mutual veto. Study shows that Bosnia’s political elites have been confrontational and non-cooperative which normally leads to political instability. However, during this period the country has achieved political stability and moderate economic development. This has been possible due to an external factor embodied in the Office of the High Representative (OHR). High Representative has made unilateral decisions and passed the laws that domestic political elites have not been able to agree upon. This has enabled the country to function in the post-Dayton period. The study benefited enormously from government documents, personal interviews, documents published by the United Nations, Office of the High Representative, local newspapers, journals, magazines and books.